Cover Feature: Broad‐Spectrum Antifungal Agents: Fluorinated Aryl‐ and Heteroaryl‐Substituted Hydrazones (ChemMedChem 1/2021). (22nd December 2020) - Thamban Chandrika, Nishad; Dennis, Emily K.; Brubaker, Katelyn R.; Kwiatkowski, Stefan; Watt, David S.; Garneau‐Tsodikova, Sylvie
Abstract : The Cover Feature shows a fluorinated aryl substituted monohydrazone attacking a field of diverse drug‐resistant pathogenic fungi, which are responsible for substantial damage to the health of immunocompromised patients. In various biological assays, this compound and its analogues exhibited exceptional promise as novel antifungal agents. More information can be found in the Full Paper by David S. Watt, Sylvie Garneau‐Tsodikova et al . Cover design by Dr. Nishad Thamban Chandrika and Dr. Sylvie Garneau‐Tsodikova.